The Corruption Eradication Commission (KPK) in the Dynamics of Constitutional Legal Politics Following Law No. 19 of 2019: Komisi Pemberantasan Korupsi dalam Dinamika Politik Hukum Ketatanegaraan Pasca Undang-Undang Nomor 19 Tahun 2019 - Andriansyah, Fery; Asmorojati, Anom Wahyu (Universitas Islam Indonesia, 2025)
Law Number 19 of 2019 concerning the Second Amendment to the KPK Law has sparked widespread controversy due to concerns that it weakens the independence and effectiveness of the Corruption Eradication Commission. The analysis is conducted within the framework of Indonesia’s constitution and political system, focusing on its alignment with the principles of the rule of law, democracy, and human rights. This study uses a normative juridical method with a qualitative descriptive approach. The findings reveal that the 2019 revision places the KPK under the executive branch, restricts technical powers such as wiretapping and searches, and limits public participation in the legislative process. Consequently, the effectiveness of corruption eradication efforts has declined, including a drop in sting operations and public trust in the KPK. Judicial Review is important to enhanced public participation, restoration of KPK’s independence, and political reform to restore the institution’s ideal function.